Simple Sequence Repeat Marker-Based Genetic Diversity and Chemical Composition Analysis of Ancient Camellia sinensis in Jiulong County, Sichuan Province, China - Huang, Haitao; He, Shuwen; Zheng, Xuxia; Shi, Daliang; Bai, Peixian; Zhao, Yun; Yu, Jizhong; Niu, Xiaojun (Genes, 2024)
Background/Objectives: The ancient tea plant germplasm resources are rich in genetic diversity and provide an important basis for the genetic diversity in tea germplasm resources. To explore the genetic diversity of ancient tea plant germplasm resources in Jiulong County, Sichuan Province. Methods: 59 ancient tea tree germplasm resources were analyzed using simple sequence repeat (SSR) molecular markers and chemical composition analysis. Results: The results showed that a total of 83 alleles were amplified by 23 pairs of SSR primers, with an average observed allele number (Na) of 3.6 and an effective allele number (Ne) of 2.335. The average Shannon information index (I) and the polymorphic information content (PIC) of the primers were 0.896 and 0.446, respectively. The results of the UPGMA cluster analysis showed that 59 ancient tea tree samples could be classified into five different subgroups. Based on the results of chemical composition analysis, two specific tea germplasm resources with high amino acid content, 10 excellent germplasm resources with tea polyphenol content over 20% and some other tea germplasm resources were identified. Conclusions: This study reveals that Jiulong’s ancient tea tree germplasm exhibits significant genetic diversity and includes valuable tea tree planting resources. These findings provide a foundational framework for the conservation, detailed exploration and sustainable utilization of these resources.